Assessment of Water Supply System Performance Indicators Based on the Customer Bill-Based Approach - Bibi, Takele Sambeto; Dinsa, Beyene Hordofa; Aragaw, Tamru Tesseme (Fakultas Teknik Universitas Brawijaya, 2023)
Significant efforts have been undertaken over the last two decades by governmental organizations and local and international non-governmental sectors to improve water supply and sanitation structures; however, there are significant challenges to the town's growth and expansion. Chiro town's population is increasing, and the community is affected by water and excreta-borne diseases as a result of a lack of proper sanitation facilities and a water supply system. In this study, billed data from Chiro Town water supply service enterprise customers have been used to assess the performance of the water distribution network over ten years (2011-2020). The findings show that the Town's water coverage is 62.9%, the water demand is 8,121.6m3/day, and the computed annual water production is 4,222.3m3/day. Residents of the town have complained about a lack of access to improved drinking water supplies, low water consumption, and sanitation facilities, particularly in the community of those who live in the town's borders and practice open defecation. For all domestic use, 16.32% and 83.68% of respondents used unprotected and protected water sources, respectively. This study suggested that strong sectoral coordination, community involvement, and sufficient financial resources were required to identify the root causes and provide an efficient water supply system in the study area.